Comparison between body fluid mode of Sysmex XN-9000 and optical microscopy for the counting of cells in ascitic fluid - Roccaforte, Vincenzo; Zavaroni, Emanuela; Russo, Rosalba Monica; Porreca, Wanda Patrizia; Proserpio, Vanessa; Liuzzi, Giammaria; Sciarini, Flavia; Bonato, Claudio; Perno, Carlo Federico; Pastori, Stefano (Journal of Laboratory and Precision Medicine, 2018)
Background: This study was designed to evaluate basic analytical performance of the body fluid (BF) mode Sysmex XN-9000 (XN-BF) and to classificate and enumerate white blood cells (WBCs) in ascitic fluid (AF) comparing with optical microscopy (OM). Methods: Sixty-six AF samples were analyzed by XN-BF and by conventional OM. The agreement between XN-9000 and OM have been evaluated with Pearson’s correlation coefficient (r) and Passing-Bablok regression, while the bias between the two methods was assessed with Bland-Altman plot analysis. The study included assessment of carryover, imprecision and linearity. Results: A good agreement was found between the results obtained by XN-BF and OM. The correlation coefficients for default parameter is comprised between 0.94 and 1.00, while for the different cells populations Pearson’s correlation is comprised between 0.80 and 0.99. The Sysmex XN-9000 BF mode displayed excellent linearity and imprecision. The carryover was negligible. Conclusions: The XN-BF shows excellent analytical performance, accurate count and cell differentiation comparable with conventional OM. Nevertheless, in all samples with abnormal WBC differential scattergram, OM continues to be the “gold standard” for a correct clinical outcome.